THE EFFECT OF PITCH ANGLE VARIATION ON PERFORMANCE OF HYBRID DARRIEUS-SAVONIUS DUAL SHAFT VERTICAL WIND TURBINE - Erwin, Erwin; Wiyono, Slamet; Nugraha, Kurnia; Putra, Rafiansyah; Triputranto, Bembi (Journal of Applied Engineering Science, 2023)
All Vertical turbines use a fixed pitch angle; the determination of the pitch angle is very influential on the characteristics of a vertical wind turbine. In the initial stages of planning a Savonius Darrieus vertical turbine, an experiment was carried out to determine the best pitch angle, and the best pitch angle was 7 degrees. In its development, many designs have changed from the initial design, so it is necessary to carry out field experiments to get the best pitch angle. The purpose of this study is to recommend the best pitch angle for hybrid Savonius Darrieus dual shaft vertical wind turbines. That suit each wind characteristic with the variable performance tip speed ratio (TSR) also (λ), coefficient of performance (Cp), mechanical power and mechanical energy. Data is collected for 8 hours in real-time, using proximity sensors, anemometers, and an Arduino Mega to record and store data on a computer. The data collection interval at every 10 seconds. The data obtained is the RPM of the rotor and the RPM of the anemometer. The results of this study are the recommended pitch angle according to the wind speed, pitch angle of 5 degrees for 1 m/s wind speed, pitch angle of 8 degrees for 2 m/s a, and pitch angle of 8 degrees for 3 m/s wind speed.